Tumor‐associated macrophages‐educated reparative macrophages promote diabetic wound healing. Issue 2 (21st December 2022) - Mu, Ruoyu; Zhang, Zhe; Han, Congwei; Niu, Yiming; Xing, Zhen; Liao, Zhencheng; Xu, Jinzhi; Shao, Ningyi; Chen, Guokai; Zhang, Junfeng; Dong, Lei; Wang, Chunming
Abstract: Nonhealing diabetic wounds, with persistent inflammation and damaged vasculature, have failed conventional treatments and require comprehensive interference. Here, inspired by tumor‐associated macrophages (TAMs) that produce abundant immunosuppressive and proliferative factors in tumor development, we generate macrophages to recapitulate TAMs' reparative functions, by culturing normal macrophages with TAMs' conditional medium (TAMs‐CM). These TAMs‐educated macrophages (TAMEMs) outperform major macrophage phenotypes (M0, M1, or M2) in suppressing inflammation, stimulating angiogenesis, and activating fibroblasts in vitro . When delivered to skin wounds in diabetic mice, TAMEMs efficiently promote healing. Based on TAMs‐CM's composition, we further reconstitute a nine‐factor cocktail to train human primary monocytes into TAMEMs C‐h, which fully resemble TAMEMs' functions without using tumor components, thereby having increased safety and enabling the preparation of autologous cells. Our study demonstrates that recapitulating TAMs' unique reparative activities in nontumor cells can lead to an effective cell therapeutic approach with high translational potential for regenerative medicine. Synopsis: Mouse and human macrophages trained by tumor‐associated macrophages (TAMs) or a cytokine cocktail exhibit improved reparative functions than conventional macrophage subtypes. Transplantation of these TAMs‐educated macrophages (TAMEMs) promotes diabetic wound healing in mice. TAMEMs and TAMs show similar expression patterns for genes regulating inflammatory resolution and tissue regeneration. TAMEMs promoted skin wound healing in both T1D and T2D mouse models, rebuilding organized vasculature comparable to that in unwounded mouse skin. A human recombinant protein cocktail—comprising osteopontin, IL‐31, IL‐10, and six other factors—recapitulated the action of TAMEMs to train human macrophages with reparative activities. Abstract : Mouse and human macrophages trained by tumor‐associated macrophages (TAMs) or a cytokine cocktail exhibit improved reparative functions than conventional macrophage subtypes. Transplantation of these TAMs‐educated macrophages (TAMEMs) promotes diabetic wound healing in mice.